1998
DOI: 10.1038/28190
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing secretion and synaptic transmission with pH-sensitive green fluorescent proteins

Abstract: In neural systems, information is often carried by ensembles of cells rather than by individual units. Optical indicators provide a powerful means to reveal such distributed activity, particularly when protein-based and encodable in DNA: encodable probes can be introduced into cells, tissues, or transgenic organisms by genetic manipulation, selectively expressed in anatomically or functionally defined groups of cells, and, ideally, recorded in situ, without a requirement for exogenous cofactors. Here we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

53
2,328
1
13

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,397 publications
(2,440 citation statements)
references
References 30 publications
53
2,328
1
13
Order By: Relevance
“…Synaptic vesicles undergo a dramatic change in pH upon vesicle fusion with the plasma membrane, a property that has been employed for the synaptic vesicle fusion sensor synaptopHluorin [26]. Both ratiometric and ecliptic pHlourins have been engineered [26], although the superecliptic synaptopHluorin has been most widely employed to address important biological questions in mammalian systems.…”
Section: Phluorins Ph-based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic vesicles undergo a dramatic change in pH upon vesicle fusion with the plasma membrane, a property that has been employed for the synaptic vesicle fusion sensor synaptopHluorin [26]. Both ratiometric and ecliptic pHlourins have been engineered [26], although the superecliptic synaptopHluorin has been most widely employed to address important biological questions in mammalian systems.…”
Section: Phluorins Ph-based Sensorsmentioning
confidence: 99%
“…Both ratiometric and ecliptic pHlourins have been engineered [26], although the superecliptic synaptopHluorin has been most widely employed to address important biological questions in mammalian systems. For example, synaptic vesicle recycling dynamics in neurons from Thy1-driven synaptopHluorin transgenic mice have been examined, providing results that challenged current models about constraints on vesicle reuse [27].…”
Section: Phluorins Ph-based Sensorsmentioning
confidence: 99%
“…1E, Bozza et al, 2004). SpH corresponds to the fusion protein between the synaptic vesicle protein VAMP-2 and a green fluorescent protein pH-sensitive (Miesenbock et al, 1998). Upon odour stimulation, vesicular release at the terminal induces an observable increase of fluorescence that reveals the pattern of nervous inputs to the OB (Fig.…”
Section: In Vivo Imaging Of Odour Evoked Signalsmentioning
confidence: 99%
“…In parallel experiments, we observed that the fluorescence of syt-eGFP is consistently brighter than that of syb-eGFP. One plausible explanation is that the fluorescence of eGFP is dimmer at lower pH (Tsien, 1998), the lumen of vesicles is acidic (pH 5.6; Miesenbock et al, 1998), and therefore it quenches the fluorescence of eGFP, as the eGFP end of syb-GFP is inside the lumen (see Fig. 1 Legend).…”
Section: Figmentioning
confidence: 99%